An investigation on wire wear in WEDM - Tosun, N; Cogun, C (Elsevier Science Sa, 2003)
In this study, the effect of cutting parameters on wire electrode wear was investigated experimentally in wire electrical discharge machining (WEDM). The experiments were conducted under different settings of pulse duration, open circuit voltage, wire speed and dielectric fluid pressure. Brass wire of 0.25 mm diameter and AISI 4140 steel of 10 mm thickness were used as tool and workpiece material. It is found experimentally that the increasing pulse duration and open circuit voltage increase the wire wear ratio (WWR) whereas the increasing wire speed decreases it. The variation of workpiece material removal rate and average surface roughness were also investigated in relation to the WWR. The variation of the WWR with machining parameters was modelled statistically by using regression analysis technique. The level of importance of the machining parameters on the WWR was determined by using analysis of variance (ANOVA) method. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: WEDM; wire wear ratio; analysis of variance